2017
DOI: 10.1111/cfs.12424
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable children's rights to participation, protection, and provision: The process of defining the problem in Swedish child and family welfare

Abstract: This study addresses the relationship between children's participation and the protection and provision offered to them by social services in Sweden. It applies a theoretical framework for analysing child welfare that is anchored in the United Nations Convention on the Rights of the Child. How child participation may affect child protection and provision is examined empirically using case documentation from 2 municipalities. The main finding is that when children are not given voice or opportunity to influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 27 publications
2
81
0
2
Order By: Relevance
“…The strong legal position of parents in Sweden, that is, the principle of voluntariness and collaboration with parents-supporting them and not intervening against their will-has been highlighted as a possible reason why children do not participate to the extent they have the right to according to law and regulations [Heimer et al, 2018]. We could not find any arguments among the respondents in our study that were focused on parents' rights as a reason to restrict children's rights to speak for themselves in court.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong legal position of parents in Sweden, that is, the principle of voluntariness and collaboration with parents-supporting them and not intervening against their will-has been highlighted as a possible reason why children do not participate to the extent they have the right to according to law and regulations [Heimer et al, 2018]. We could not find any arguments among the respondents in our study that were focused on parents' rights as a reason to restrict children's rights to speak for themselves in court.…”
Section: Discussionmentioning
confidence: 99%
“…Others argue that participation is a way to protect children, as participation in itself could improve children's confidence, self-efficacy, and self-worth [Weisz, Wingrove, Bel, & Falth-Slaker, 2011]. In addition, the two competing discourses of participation and protection could exist within the same context at the same time [De Godzinsky, 2014;Heimer, Näsman, & Palme, 2018;Tisdall, 2016].…”
Section: Different Levels Of Participationmentioning
confidence: 99%
“…To what extent children are involved in cases of relevance to them affects the way problems are described and explained as well as what kind of help CWS offer families. Heimer et al (2017) found when interviewing family workers that without exception they based their work on the parents' way of describing the problems. Further, they found that a variety of problems and concerns were 'reframed' into problems with structure, routines and border setting, making them fit for parent counselling within a family treatment frame (Heimer et al 2017).…”
Section: Marginalization Of the Childmentioning
confidence: 99%
“…Heimer et al (2017) found when interviewing family workers that without exception they based their work on the parents' way of describing the problems. Further, they found that a variety of problems and concerns were 'reframed' into problems with structure, routines and border setting, making them fit for parent counselling within a family treatment frame (Heimer et al 2017). Likewise, Bakketeig (2015) found that while children were often heard at a very early stage, information sought was more about how they were doing in general and less about what kind of help they wanted.…”
Section: Marginalization Of the Childmentioning
confidence: 99%
“…This has been evidenced both in scientific research as well as in the implementation of child participative approaches within child protection and welfare institutions all over the world (Healy, Darlington, & Yellowlees, 2012). Child participation has proven to be essential to deliver responsive care and as a result, more effective and sustainable interventions (Dedding, 2009;Heimer, N€ asman, & Palme, 2017;Sinclair, 2004;Van Bijleveld, Dedding, & Bunders-Aelen, 2015). Additionally, child participation has proven to build empowerment, a sense of control (Bell, 2002) and a higher self-esteem, whereas a lack of participation might lead to disempowerment and a lower self-esteem (Littlechild, 2000;Vis, Strandbu, Holtan, & Thomas, 2011).…”
Section: Introductionmentioning
confidence: 99%